2018
DOI: 10.1080/19420862.2018.1476815
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study of domain rearrangements of single-chain bispecific antibodies to determine the best combination of configurations and microbial host cells

Abstract: Small bispecific antibodies (bsAbs) are important therapeutic molecules and represent the first bsAb format approved by the United States Food and Drug Administration. Diabody (Db), a small bsAb format, has four possible domain orders; we previously reported the differences in the expression levels and cancer growth inhibition effects upon rearranging the domain order of this format. However, there have been no comprehensive reports on domain rearrangements of bispecific single-chain Db (scDb) and tandem singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…We have reported that rearranging the domain order affected the cancer growth inhibitory activity of humanized bsDb targeting EGFR and CD3 [ 16 ]. The highest inhibitory effect was observed for the LH type of hEx3-Dbs, and similar tendencies were confirmed with other bsDbs targeting EGFR and CD3 [ 17 , 18 , 25 ]. CD3 co-localizes with a relatively bulky TCR, and a recent study using cryo-electron microscopy clearly revealed the large, fully assembled structure of CD3 and TCR [ 20 ].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We have reported that rearranging the domain order affected the cancer growth inhibitory activity of humanized bsDb targeting EGFR and CD3 [ 16 ]. The highest inhibitory effect was observed for the LH type of hEx3-Dbs, and similar tendencies were confirmed with other bsDbs targeting EGFR and CD3 [ 17 , 18 , 25 ]. CD3 co-localizes with a relatively bulky TCR, and a recent study using cryo-electron microscopy clearly revealed the large, fully assembled structure of CD3 and TCR [ 20 ].…”
Section: Discussionsupporting
confidence: 81%
“…However, we could not isolate and purify soluble hEx16-scDbs for further investigation by using an E. coli expression system. We then used the Brevibacillus choshinensis expression system, which offers several advantages [ 22 , 23 , 24 ], as demonstrated in our recent preparation of small bispecific antibodies, including hEx3-scDbs [ 25 ]. In the present study, we confirmed the successful preparation of soluble hEx16-scDbs using B. choshinensis , followed by gel filtration chromatography and SDS-PAGE analysis under reducing conditions ( Figure 3 C,D and Figure S3A,B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By ligating T-cells with target cells and activating T-cells through CD3, blinatumomab can induce the killing of CD19-expressing B-cells including malignant B-cell leukemia and lymphoma [4]. The order of variable domains is critical for the production of functional BiTE [5], while the length of the inter-scFv linker may either be short (GGGGS) or long ((GGGGS) 3 ) without significantly affecting its tumor-killing activity [6]. Of course, it is unlikely that there exists a single optimal molecular configuration for all tandem scFvs, because the effect of variable domain order on the functionality of scFv differs among antibodies, and close proximity of two scFvs connected by a short linker may interfere with the antigen binding activity of certain antibodies.…”
Section: Fragment-based Bsabsmentioning
confidence: 99%